Kontestasi Epistemologis dalam Penafsiran Ru’yatullāh: Analisis Komparatif al- Zamakhsyari dan al-Ṭabari atas QS al-Qiyāmah [75]: 22–23 - Nur Intan Rahmadani; Syafruddin; Radhiatul Hasnah (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2026)
This article analyzes the epistemological contestation in the interpretation of QS al-Qiyāmah [75]: 22–23 through a comparative study of al-Kasysyāf by al-Zamakhsharī and Jāmiʿ al-Bayān by al-Ṭabarī. Studies on the differences in the interpretation of the verses on ru’yatullāh have been widely conducted; however, most of them remain limited to identifying interpretive differences without explaining the epistemological mechanisms that construct such meanings. This research employs a comparative hermeneutics approach with the theory of ikhtilāf al-mufassirīn as the analytical framework. The primary data consist of the interpretations of both exegetes on QS al-Qiyāmah [75]: 22–23, which are analyzed through the identification of argumentative structures, epistemic bases, and processes of meaning legitimization employed by each exegete. The findings show that the difference in the meaning of the word nāẓirah is not merely determined by linguistic preference, but is shaped by the epistemological horizon of each exegete. Al-Zamakhsharī reconstructs meaning through linguistic rationality aligned with Muʿtazilite theological principles, interpreting nāẓirah as al-intiẓār (waiting/expectation), whereas al-Ṭabarī constructs the authority of meaning through the selection of transmitted reports (riwāyah) and the mechanism of tarjīḥ, thereby affirming the literal meaning of ru’yah (vision). This study demonstrates that differences in Qur’anic exegesis (ikhtilāf al-tafsīr) represent manifestations of epistemological construction within the classical tafsir tradition.